Germline alterations in patients with biliary tract cancers: A spectrum of significant and previously underappreciated findings. Issue 9 (3rd February 2020) - Maynard, Hannah; Stadler, Zsofia K.; Berger, Michael F.; Solit, David B.; Ly, Michele; Lowery, Maeve A.; Mandelker, Diana; Zhang, Liying; Jordan, Emmett; El Dika, Imane; Kemel, Yelena; Ladanyi, Marc; et al.
Abstract : Background: With limited information on germline mutations in biliary tract cancers, this study performed somatic and germline testing for patients at Memorial Sloan Kettering Cancer Center with known biliary tract carcinoma with the aim of determining the frequency and range of pathogenic germline alterations (PGAs). Methods: Patients with biliary tract carcinoma were consented for somatic tumor and matched blood testing of up to 468 genes via the Memorial Sloan Kettering Cancer Center Integrated Mutation Profiling of Actionable Cancer Targets next‐generation sequencing platform. A germline variant analysis was performed on a panel of up to 88 genes associated with an increased predisposition for cancer. Demographic and diagnostic details were collected. Results: Germline mutations were tested in 131 patients. Intrahepatic cholangiocarcinoma was the most common cancer (63.4%), and it was followed by gallbladder adenocarcinoma (16.8%), extrahepatic cholangiocarcinoma (16%), and otherwise unspecified biliary tract cancer (3.8%). Known and likely PGAs were present in 21 patients (16.0%), with 9.9% harboring a PGA in a high/moderate‐penetrance cancer predisposition gene. Among high‐penetrance cancer susceptibility genes, PGAs were most commonly observed in BRCA1 and BRCA2 (33.3%), which made up 5.3% of the entire cohort, and they were followed by PALB2, BAP1, and PMS2 . Mutations in ATM, MITF, and NBN, moderate‐penetrance cancer susceptibility genes, were identified in 1 patient each. There was no observed difference in the types of mutations among the subtypes of biliary tract cancer. Conclusions: The frequency of PGAs found was comparable to existing data on the prevalence of germline mutations in other solid tumor types with matched tumor analysis. This provides support for the role of the BRCA1/2, ATM, and BAP1 genes in biliary tract cancer susceptibility. Abstract : The frequency of pathogenic germline alterations is comparable to existing data on such prevalence in other solid tumor types with matched tumor analysis. This provides support for the role of the BRCA1/2, ATM, and BAP1 genes in biliary tract cancer susceptibility.